Combined spectral and stimulated luminescence study of charge trapping and recombination processes in α-Al2O3:C - Nyirenda, Angel Newton (Rhodes University, Faculty of Science, Department of Physics and Electronics, 2018)
The main objective of this project was to gain a deeper and better understanding of the luminescence processes in a-Al₂O₃:C, a highly-sensitive dosimetric material, using a combined spectral and stimulated luminescence study. The spectral studies concentrated on the emission spectra obtained using X-ray induced radioluminescence (XERL), thermoluminescence (XETL) and time-resolved X-ray excited optical luminescence (TR-XEOL) techniques. The stimulated luminescence studies were based on thermoluminescence (TL), optically stimulated luminescence (OSL) and phototransferred TL (PTTL) methods that were used in the study of the radiation-induced defects at high beta-doses and the deep traps, that is, traps with thermal depths beyond 500°C. The spectral and stimulated luminescence measurements were carried out using a high sensitivity luminescence spectrometer and a Ris0 TL/OSL Model DA-20 Reader, respectively. The XERL emission spectrum measured at room temperature shows seven gaussian peaks associated with F-centres (420 nm), F+-centres (334 nm), F2+-centres (559 nm), Stoke's vibronic band of Cr3+ (671 nm), Cr3+ R-line emission (694 nm), anti-Stokes vibronic band of Cr3+ (710 nm) and an unidentified emission band (260-300 nm) which we associate with hole recombinations at a luminescence centre. The 694-nm R-line emission from Cr3+ impurity ions is most likely due to recombination of holes at Cr2+ during stimulated luminescence and as a result of an intracentre excitation of Cr3+ in photoluminescence (PL) due to photon absorption. The Cr3+ emission decreases in intensity, whereas the intensity of F-centre emission band is almost constant with repeated XERL measurements. Depending on the amount of X-ray irradiation dose, both holes and/or electrons may take place in the emission processes of peaks I (30-80°C), II (90-250°C) and III (250-320°C) during a TL readout, albeit, electron recombination is dominant regardless of dose. At higher doses, the XETL emission spectra indicate that the dominant band associated with TL peak III (250-320°C) in the material, shifts from F-centre to Cr3+. Using the deep-traps OSL, it has been confirmed that the main TL trap is also the main OSL trap whereas the TL traps lying in the temperature range of 400-550°C constitute the secondary OSL traps. There is evidence of strong retrapping at the main trap during optical stimulation of charges from the secondary OSL traps and the deep traps and that the retrapping occurs via the delocalized bands. At high-irradiation beta-doses, aggregate defect centres which significantly alter the TL and OSL properties, are induced in the material. The induced aggregate centres get completely obliterated by heating a sample to 700°C. The radiation-induced defects cause the main TL peak to shift towards higher temperatures, increase its FWHM, reduce its maximum intensity and cause an underestimation of both the activation energy and order of kinetics of the peak. On the other hand, the OSL response of the material is enhanced following a high-irradiation dose. During sample storage in the dark at ambient temperature, charges do migrate from the deep traps (donors) to the main and intermediate traps (acceptors) and that the major donor traps during this charge transfer phenomenon lie between 500-600°C.
Keywords: Luminescence; Thermoluminescence; Luminescence spectroscopy; Carbon-doped aluminium oxide; Radioluminescence; Time-resolved X-ray excited optical luminescence